Growth performance of water spinach Ipomoea aquatica and freshwater prawn Macrobrachium rosenbergii grown in aquaponic and hydroponic units - Alam, Zeba F.; Karen Avena; Lorenzo Sales; Denise Suemith; Riane UY (Indian Journal of Fisheries, 2022)
In the present study, attempts were made to optimise water spinach (Ipomoea aquatica) in combination with freshwater prawns (Macrobrachium rosenbergii) to be grown under aquaponics culture conditions, especially as an indoor set-up suitable for urban dwellings. A comparison of the morphometric parameters such as linear growth and number of leaves of plants and the survival rate under the soil, aquaponics, aquarium and hydroponics units simultaneously per cycle was done to establish the stability of the system. The water spinach grown under the aquaponics set-up showed significant growth compared to the hydroponics set-up but was less than that of the soil units. Significantly higher growth of freshwater prawns was also recorded in the aquaponics unit compared to the aquarium unit. Though further investigations are still needed to find factors that can give optimum produce, the researchers propose that standardised aquaponic units for water spinach and freshwater prawns can be a safe option for urban households as a sustainable farming practice. Keywords: Food security, Hydroculture, Symbiotic growth, Urban farming